Potential roles of fibroblast growth factor 21 in the brain - Sa-nguanmoo P. (2017)
© 2016, Springer Science+Business Media New York. Fibroblast growth factor 21 (FGF21) is an endocrine hormone, playing an important role in the regulation of metabolism. FGF21 is primarily expressed by several tissues, including liver, pancreas, thymus, heart, muscle, adipose tissue, and brain. In addition to the effects of FGF21 in lowering glucose and lipid levels, increasing insulin sensitivity and regulating energy homeostasis in rodents and non-human primate models of diabetes and obesity, previous reports have demonstrated that FGF21 also plays an important role in the brain involving it in potential effects in metabolic regulation, neuroprotection and cognition. In this review, the current available evidence from both in vitro and in vivo investigations regarding the roles of FGF21 and its function in the brain are comprehensively summarized. In addition, the mechanistic insights regarding the roles of FGF21 in the brain and its potential neuroprotective benefits are also presented and discussed.